Successful Separation of Conjoined Twins: Experience of a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2018)
Background: The separation of conjoined twins presents a unique challenge to many pediatric surgical specialties. Meticulous preoperative investigations, planning and multidisciplinary team approach led by pediatric surgeon contribute to the success of surgical separation. The aim of this study is to share our experiences of one hospital to enhance skill for treating conjoined twins regarding anatomic variations, investigations, surgical aspects, outcomes and rehabilitation.Methodology: All cases of symmetrical conjoined twins who were treated from July 2009 to February 2018 at the Pediatric Surgery Department of Dhaka Medical College Hospital, Dhaka, Bangladesh were included in this prospective type of study. All types of parasitic twins were excluded. Prenatal ultrasound diagnosis, gender, birth weight, anatomy of the twins, the age and weight at the time of the separation surgery, the length of surgery, the duration of anesthesia during the separation surgery, a detailed description of the separation surgery, the type of skin closure, postoperative complications and death were studied.Results: There were three sets of thoraco-omphalo-ischiopagus twins, one set of thoraco-omphalopagus twins, one set of pygopagus twins. Three sets had no prenatal visit or ultrasound evaluation. Two sets of conjoined twins were failed to separate due to the complexity of the organs that were shared by both twins and instability leading to death. Only one set of pygopagus twins was successfully separated. Emergency colostomies were done on pygopagus twins due to the presence of anorectal anomalies. The surgical survival rate was 100%. One set of twins who did not undergo separation due to refusal of treatment was currently alive. One set of twins was under evaluation and currently alive.Conclusion: The overall success of conjoined twin separation depends on the experience and preparedness of treating team led by pediatric surgeon and resources available at the hospital. No single discipline can expect to have all the necessary talents.Bangladesh J Child Health 2018; VOL 42 (2) :73-78